CORE SEMANTIC FEATURES OF INTERIOR DESIGN TERMS (IN THE EXAMPLE OF ENGLISH AND UZBEK LANGUAGES). - Melikova Gavhar (Ta'lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT: Core semantic features of interior design terms encompass various elements crucial to the discipline. They often denote spatial concepts, materials, aesthetics, and functionality. Terms like "balance," "proportion," and "scale" highlight the spatial arrangement and visual harmony within a space. "Texture," "color," and "lighting" emphasize the sensory aspects and mood creation. "Furniture," "fixtures," and "accessories" denote tangible elements contributing to functionality and style. "Style," "theme," and "concept" refer to overarching design principles guiding the overall aesthetic direction. These semantic features collectively define the language of interior design, facilitating effective communication and conceptualization within the field.